Mapping genomic organization by field inversion and two-dimensional gel electrophoresis: application to the murine T-cell receptor gamma gene family. - Woolf, T (1988)
A new two-dimensional gel electrophoresis technique has been developed for the mapping of multigene families. Resolution in the first dimension is based on the generation of large size DNA fragments by infrequently-cutting restriction enzymes, and separation of these fragments by field inversion gel (FIG) electrophoresis. A second restriction enzyme digestion is then carried out with the separated DNA fragments in the agarose gel. Standard gel electrophoresis in the second dimension allows one to estimate the number of hybridizing genes contained in each large DNA fragment. We have also developed a novel method to increase the separation, resolution and hybridization signal in the second dimension by condensing the bands from the first dimension into spots. As an example, we have applied these techniques to determine the organization of the murine T-cell receptor gamma locus. The murine gamma gene family was found to be contained on two DNA fragments encompassing 195 kilobases of DNA. The two-dimensional gel electrophoresis method is particularly useful in the analysis of the organization of multigenic families where single copy probes are not readily available, and should extend the potential usefulness of field inversion gel electrophoresis in gene mapping.